Analisis Penyusunan Patient Safety Phatway Coronary Artery Disease (CAD) Pro Percutaneous Coronary Intervention (PCI) di Instalasi Brain and Heart Centre RS Dr. Moh. Hoesin Palembang Tahun 2015 - Harjito, Harjito (UI Scholars Hub, 2016)
This studydiscusses the preparation of patient safety phatway Coronary artery disease (CAD) pro Percutaneous Coronary Intervention (PCI) in the Installation Brain And Heart Centre dr. Moh. Hoesin Palembang.Research a descriptive analytic with cross sectional observation through depth interviews with admissions personnel, nurses and doctors The results of research suggest especially the Committee on quality and patient safety Hospitals need to further improve and develop a patient safety program to make safety Patient Pathway most particularly diseases, have a high risk and has cost expensive.and established a working group to evaluate the implementation of the application of patient safety in hospitals